Excess Liquidity Creation of Banks and Financial Market Peaks - Patrick Weber (Credit and Capital Markets – Kredit und Kapital, 2016)
Mutually reinforcing dynamics between the market liquidity of financial assets and the funding liquidity risks of financial intermediaries were one of the reasons why asset prices declined so significantly with the onset of the financial crisis in 2007. Based on this observation, I show how an excessive rate of funding liquidity risk-taking by financial intermediaries can be used as a timing measure for an upcoming peak of equity market prices in Germany for the time period 1973 to 2010. Funding liquidity risk-taking is thereby defined as the degree of liquidity creation by banks. The working hypothesis is that if banks create liquidity at an excessive rate, then the German equity market will reach a significant peak at or shortly after the peak in the liquidity creation activity of the banking system. The proposed early warning indicator predicted all peaks on the equity market in Germany for the time period 1973 to 2010 with an average lead time of 2.9 months. Hence, the rate of liquidity creation seems to provide very useful information about the future state of financial markets. The early warning indicator can be applied in real-time. – – Exzessive Liquiditätsschöpfung der Banken und Finanzmarkthöchststände Sich selbst verstärkende Effekte zwischen der Liquidität auf Finanzmärkten und den Refinanzierungsrisiken von Finanzintermediären waren einer der Gründe warum Wertpapierpreise mit dem Einsetzen der Finanzkrise im Jahr 2007 so stark eingebrochen sind. Auf Basis dieser Beobachtung zeigt dieser Beitrag wie ein exzessiver Aufbau von Refinanzierungsrisiken des deutschen Bankensystems als ein Maß für das Timing von signifikanten Höchstständen von Aktienkursen in Deutschland für den Zeitraum 1973 bis 2010 genützt werden kann. Die Refinanzierungsrisiken resultieren dabei aus der Liquiditätsschöpfung des Bankensektors. Die Arbeitshypothese dieses Artikels ist, dass der Zeitpunkt zu dem die Liquiditätsschöpfung des Bankensystems exzessiv wird und einen Höchststand erreicht, sich kurze Zeit später ein Höchststand auf dem Aktienmarkt einstellt. Es zeigt sich, dass der in diesem Beitrag entwickelte Frühwarnindikator alle signifikanten Höchststände des DAX 30 für einen Zeitraum von 1973 bis 2010 ca. 2,9 Monate im Voraus identifizieren konnte. Daraus folgt, dass die Rate mit der Banken Liquidität schöpfen, besonders wenn sich diese in einem exzessiven Bereich befindet, nützliche Informationen über zukünftige Finanzmarktentwicklungen liefern kann. Der in diesem Beitrag entwickelte Frühwarnindikator kann in Echtzeit angewendet werden.
Keywords: G01; G17; E44; E51; 330; Early warning indicator for distress on financial markets; Asset prices; Liquidity creation of financial intermediaries; Funding liquidity risks